ASPECTS REGARDING LOCUS IN MECHANICS - Răzvan Bogdan ITU (Fiabilitate şi Durabilitate)
Essentially, locus problems are problems of finding characteristics equivalent to those by which a certain intersection is given, in other words, the equality problem of two intersections. The paper presents aspects regarding the locus in plane – parallel movement in kinematic mechanics, namely the circle of inflections and the turning back circle.